Movement disorders in childhood - Singer, Harvey S.; Mink, Jonathan W.; Gilbert, Donald L. (Pediatric neurologist); Jankovic, Joseph (Academic Press, an imprint of Elsevier, 2022)
"Movement Disorders in Childhood, Third Edition provides the most up-to-date information on the diseases and disorders that affect motor control, an important area of specialization within child neurology. In this new edition, each chapter has been fully revised to include all of the latest scientific and therapeutic advances. Updates include new insights in motor development, control, goal-directed and habitual behaviors, classifications of movements and their complex and integrated circuitry. The authors also discuss developments in pathophysiologic mechanisms, immunology and metabolic disorders. New chapters include coverage of genetics of movement disorders and movement disorders in psychiatric conditions. Appendices include an updated and revised drug index and genetic search strategy. An updated Companion website hosts selected educational videos to help diagnose movement disorders" -- publisher's description.